Socio-Demographic Characteristics of Patients with Ocular Infection in Northern India - Khan, Shariq Wadood; Raza, Adil; Zakir, Shaik Mohammed; Zubair, Mohd Yasir; Khan, Haris Manzoor; Shahid, Mohammad (International Journal of Human and Health Sciences (IJHHS), 2023)
BACKGROUND: The microbiological and epidemiological patterns seem to vary with the patient population, site of infection, geographic location and it may also change over time. Hence, an understanding of the epidemiological features, risk factors and etiological agents that occur in a specific region are important in rapid recognition, timely institution of empirical therapy, optimal management and prevention of these infections. OBJECTIVE: To study association of various socio-demographic factors with ocular infections and microbiological positivity rates of collected samples at our tertiary care centre. METHODS: This study was conducted in the Department of Microbiology & Institute of Ophthalmology, Jawaharlal Nehru Medical College, Aligarh Muslim University (A.M.U.), Aligarh from July 2018 to February 2021. RESULTS: Out of 350 patients diagnosed with ocular infections in the study, 207(59.14%) were male patients, and 143 (40.8%) were female. Similar number of patients presented in each group. The clinical diagnosis of the infective conditions of the eye ranged from mostly innocuous Conjunctivitis to sight threatening Corneal ulcers and Endophthalmitis. The overall culture-positivity rate for bacterial isolation was 54.57% (191/350). CONCLUSION: There is slight gender preponderance towards males for infective ocular conditions. In this study, the most prevalent clinical condition was ocular adnexal bacterial infections, followed by corneal ulcers. From 350 patients with ocular infections, 54.57% were culture-positive. Our study provides pattern of different ocular infections in OPD and IPD settings which may be may be of use to clinicians in their day to day practice. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S159-S167